The impact of breeding Yellow-Legged Gulls on vegetation cover and plant composition of Grey Dune habitats - Portela, Diogo (2023)
The establishment of large populations of yellow-legged gull Larus michahellis in coastal and urban areas can lead to strong changes in vegetation cover and composition through creating physical disturbance in the vegetation and impacting the soil quality through defecation. In this study, we evaluated the effects of breeding yellow-legged gull populations on tall and short vegetation cover and plant species composition in old (occupied for 13 years) and new (occupied for 3 years) colony sites in grey dunes of the Algarve, southern Portugal. In each site, sampling plots were used to measure the percentage of vegetation cover in areas with and without breeding gulls. In the old colony site, the cover by tall vegetation was substantially reduced and the cover by short vegetation substantially increased in the areas where gulls are breeding in comparison with the adjacent areas. In the new colony sites, there were only minor differences. The increase in cover of short vegetation in the breeding area of the old colony site was mostly by nitrophilous species (Paronychia argentea and Malcolmia littorea) and should be explained by the decrease in vegetation cover of tall plant species and by feces deposition. Tall and slow-growing species Suaeda maritima and Helichrysum italicum covers were negatively affected. Our results showed that yellow-legged gulls affected vegetation cover and composition of grey dunes after 3 years of consecutive breeding, and this should be considered in the management of these habitats where breeding yellow-legged gulls are increasing.